Pengalaman Komikus Indonesia Dalam Memasarkan Komik Digital Melalui Instagram - Supradaka, Supradaka; Yunarti, Susi (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2023)
Comic works are increasingly being found on Instagram and are being used as part of businesses in the digital era, because most comic printing businesses in Indonesia have experienced difficulties/failed, just like any publishing sector in the world which has been affected by digital disruption. Comic works will only grow if they have readers and buyers. For this reason, comic artists need to have a strong understanding of digital marketing concepts. The aim of this research is to find out the experience of Indonesian comic artists in marketing digital comics via Instagram. This research uses a qualitative descriptive approach with phenomenological methods on Indonesian comic creators/comic artists. The research results obtained show that the positive experience gained by Indonesian comic artists in marketing digital comics through Instagram namely comic artists are more widely known by consumer, can build a reputation, attract attention and mobilize consumer actions to make purchases.